Implementation of Ergonomic Work System for Occupational Diseases in Red Onion Porters in Banjarejo Village - Ahmad Farid Naylul Muwafiq; Mayta Sari Dwianggimawati (Universitas STRADA Indonesia, 2021)
Occupational Safety and Health (K3) issues in general in Indonesia are still often ignored. This is indicated by the still high number of work accidents. In 2014, there were 40,694 cases of Occupational Diseases (PAK) in Indonesia. For this reason, researchers are interested in conducting research on